Pemanfaatan Rak Digital sebagai Perpustakaan Online dalam Kepemimpinan Islam Bagi Anak Sekolah Dasar - Azkia Nurul Fauziah; Delusi Andes; Sabrina Dwi Oktaviani; Ani Nur Aeni (Yayasan Letiges Konsultan Sosial, 2023)
The availability of adequate learning media is a demand for learning at this time, where technology is proliferating along with discoveries in the digital field. Learning like today, of course, many material files are shared in learning activities. This is the basis for the need to make an online library-based learning development design, namely a digital shelf to introduce Islamic Leadership for Elementary School children so that the storage of material files or E-Books is not scattered. This research uses the D&D (Designed and Development) method. This D&D model is usually used to explore a design, development, and assessment operation intended to create an empirical basis to produce products and tools, whether used in teaching and learning activities or not in learning and building new models. The trial was conducted to determine the users' responses, namely teachers and students in grades 5 and 6 in elementary school. The study's results were from the student's point of view; on average, they liked the digital shelf because it was more accessible and new to them. Then from the teacher's point of view, they also like the digital shelf because it is considered an innovative product for learning at school.